Food shopping, preparation and consumption practices in times of COVID-19: case of Lebanon. Issue 2 (15th June 2021) - Ben Hassen, Tarek; El Bilali, Hamid; Allahyari, Mohammad S.; Charbel, Laurence
Abstract : Purpose: Right after announcing the first cases, several governments worldwide have implemented stringent measures to stop the spread of COVID-19. This disruption in individuals' daily routines transformed food consumption habits. Accordingly, the purpose of this paper is to examine the effects of the COVID-19 pandemic on food consumption, diet and food shopping behaviors in Lebanon. Design/methodology/approach: The paper draws upon an online survey in Lebanon administered in Arabic and English through the Survey Monkey platform in the period of July 15—August 5, 2020, with 201 adults. The survey findings were analyzed using descriptive statistics, a paired sample t -test and a Phi correlation test. Findings: The research underlined numerous key consumer tendencies that are currently affecting diet and food behavior in Lebanon. Indeed, the study outcomes suggested (1) a move toward healthier diets; (2) a rise in the consumption of domestic products due to food safety concerns; (3) a change in the grocery shopping behaviors (with a rise in online shopping); (4) a surge of food stockpiling; and (5) a decrease in household food wastage. Surprisingly, COVID-19 seems to generate several positive changes toward more sustainable and healthier consumption patterns in Lebanon. Research limitations/implications: These findings contribute to the clarification and critical analysis of the impacts of COVID-19 on food behaviors in Lebanon, which would have several policy implications. Originality/value: The findings of this first study contribute to the clarification and critical analysis of the impacts of COVID-19 on food behaviors in Lebanon, which would have several policy implications.